The Influence of Using YouTube Application Towards Students’ Speaking Skill at The Eighth Grade of SMPN 2 Banjarsari Lebak Banten in Academic Year 2021/2022 - Apriliyanti, Regina; Gumelar, Rizdki Elang; Riandi, Riandi (Universitas Mathla'ul Anwar Banten, 2023)
The purpose of this study is to find out the influence of the YouTube application towards Students' Speaking skill. The method used in this study is a quantitative approach with a quasi-experimental research design. The sample for this research was 54 students of class VIII SMPN 2 Banjarsari for the 2022 academic year. They were class VIII A as the experimental class and VIII B as the control class. Each class consists of 27 students. The experimental class uses the YouTube application method, while the control class uses video snacks. The results of this study indicate that there is an influence of the YouTube application towards students' speaking skill. Supported by the results of the average post-test score in the experimental class is (67.04), while the average score of the control class is (59.26) and the average pre-test score in the experimental class is (55.56) while the average value of the control class pre-test was (55.37), then testing the hypothesis utilizing matched example t-test on SPSS 22 for windows showed that the worth of t include > t-table in the exploratory class was -7.510. Additionally, the significance level is below 0.05 (p=0.00-0.05 in the experimental class). The alternative hypothesis (Ho) is accepted, according to the findings. Therefore, the researcher concluded that there is a significant influence of the YouTube application towards students’ speaking skill.